Analisis Kesulitan Menulis pada Siswa Kelas I di Sekolah Dasar Negeri Tanjung Jati 2 - Puspita Utami, Putri; Tri Yulianto, Muhammad Zanuar; Jannah, Ana Naimatul; Nurhalima, Nurhalima (Indo-MathEdu Intellectuals Journal, 2025)
Writing is the process of conveying ideas or ideas as a whole from all active activities expressed through letters and numbers that are easily understood by others. This study aims to find out children who have difficulty writing at SDN Tanjung Jati 2 in grade 1, The research method used in this study is a qualitative method. The subjects of this study were grade 1 students at SDN Tanjung Jati 2. Data collection techniques used in this study include observation, interviews, and documentation. The data analysis technique in this study uses source triangulation techniques, which aims to check the consistency and validity of information obtained from various sources. The results of the study of students who have difficulty writing letters and numbers are because students do not fully know or remember the letters from A to Z, difficulty writing letters into a word or sentence, errors in writing letters, reversal of letters, such as b becomes d, errors in writing numbers, and pencil pressure in writing.